LVTM: A lightweight blockchain-based V2G terminal trust management method - Jiexiao Yu; Zhibiao Guo; Liying Yu; Ting Yang (CSEE Journal of Power and Energy Systems)
As an important part of the smart grid (SG), Vehicle-to-Grid (V2G) has significantly advanced the development of the grid. However, the open nature of V2G system itself and the deployment of charging piles (CPs) increase the difficulty of terminal control and leave the grid vulnerable to attacks. The existing security schemes of V2G mostly consider the threat of external attacks and conduct defense strategies such as identity authentication and key management, which cannot resist internal attacks initiated by selfish or captured terminals that have passed authentication. In this paper, we propose a lightweight block-chain-based trust management method for V2G terminals. Specifically, we provide a blockchain-based V2G trust management architecture. A V2G terminal adaptive trust calculation model based on information entropy is established, which provides a basis for accurate trust calculation. Considering that, although the on-chain data is tamper-proof, the existing blockchain technology lacks the means to verify the authenticity of the source data before it is uploaded to the chain, a new blockchain consensus mechanism is designed. Wherein five consensus guidelines ensure that only real trust parameters can be written on the chain. In this way, malicious terminals can be identified by consensus screening and trust calculation, thereby taking control measures. Moreover, to avoid redundant hash operations during the trust parameter upload process, Merkle Mountain Range (MMR) is introduced to optimize the block structure. The experimental results show that in comparison to existing methods, LVTM is very resistant to internal attacks, and has lower communication costs and computing overhead.